Pengembangan Perangkat Pembelajaran Fisika Berbasis Virtual Laboratorium Pada Materi Listrik Di SMK: Development of Physics Based Learning Devices Virtual Laboratory on Electrical Material at SMK - Idhar Khaira; Maison Maison; Jefri Marzal (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
Physics is a subject that does not only prioritize students’ understanding of material aspects but also improve students' thinking skills. It is expected that students are not only capable and skilled in the field of psychomotor, but also able to think systematically, objectively, and creatively. In order to achieve the objectives learning physics needs to be supported by practicum. However, there are still a number of obstacles in undertaking practicum, one of which is inadequate laboratory equipment. This study aims to develop learning media for class XII physics material on topic of dynamic electricity that develop and enhance students' science process skills in the laboratory. This type of research is a development research using the ADDIE development model. Validation is done by two experts, the material expert and media expert, aiming to get comments and suggestion to produce interesting and high quality media. Based on the experts’ assessment as well as peer teacher and students trial, the developed media is considered as feasible that can be applied to facilitate physics learning for students of class XII.